2015
DOI: 10.1111/anae.13016
|View full text |Cite
|
Sign up to set email alerts
|

Fibreoptic vs videolaryngoscopic (C-MAC®D-BLADE) nasal awake intubation under local anaesthesia

Abstract: SummaryNumerous indirect laryngoscopes have been introduced into clinical practice and their use for tracheal intubation under local anaesthesia has been described. However, a study comparing indirect laryngoscopic vs fibreoptic intubation under local anaesthesia and sedation appears lacking. Therefore, we evaluated both techniques in 100 patients with an anticipated difficult nasal intubation time for intubation the primary outcome. We also assessed success rate, glottic view, Ramsey score, and patients' and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
94
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 29 publications
2
94
1
3
Order By: Relevance
“…Kramer A et al [13] compared Fiberoptic versus C-MAC D-BLADE for awake nasal intubation and concluded that the time to tracheal intubation was significantly shorter with C-MAC D-BLADE (38 s for D-BLADE vs. 94 s for Fiberoptic) and the 2 instruments showed insignificant variance regarding success rate. They showed that C-MAC D-BLADE was superior to Fiberoptic and this was similar to our results but the details were different as they used awake nasal intubation but we used oral intubation under general anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Kramer A et al [13] compared Fiberoptic versus C-MAC D-BLADE for awake nasal intubation and concluded that the time to tracheal intubation was significantly shorter with C-MAC D-BLADE (38 s for D-BLADE vs. 94 s for Fiberoptic) and the 2 instruments showed insignificant variance regarding success rate. They showed that C-MAC D-BLADE was superior to Fiberoptic and this was similar to our results but the details were different as they used awake nasal intubation but we used oral intubation under general anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…In their comparative study of fibreoptic and videolaryngoscope-guided awake nasotracheal intubation, Kramer and colleagues report an equal failure rate (4%) in each group, but for different reasons [1].…”
Section: Awake Nasal Intubation: the Gag Reflex And Failure Of Videolmentioning
confidence: 99%
“…about their study comparing videolaryngoscopy and bronchoscopyassisted nasal intubation in patients with predicted difficult airways [1]. Firstly, we think that there is a clear difference in the management of patients with anatomically 'difficult' airways compared with those with potentially obstructed airways, but it is not clear from the authors' results who had the former and who the latter.…”
mentioning
confidence: 94%